Novel chaetospirolactone and orsellide F from an endophytic fungus Chaetomium sp. Issue 3 (4th March 2018) - Xu, Qin-Lan; Xiao, Yong-Sheng; Shen, Ye; Wu, Hui-Min; Zhang, Xuan; Deng, Xin-Zhao; Wang, Ting-Ting; Li, Wei; Tan, Ren-Xiang; Jiao, Rui-Hua; Ge, Hui-Ming
Abstract: Chaetospirolactone (1 ), a novel spiro-lactone bearing a rare 1-oxaspiro [4.4] non-7-ene-2, 6-dione skeleton, and orsellide F (2 ), together with six known compounds (3–8 ), were isolated from an endophytic fungus Chaetomium sp . NF00754. Their structures were determined by interpretation of spectroscopic data. The absolute configurations of1 and2 were established by analysis of single X-ray crystallographic data and CD spectra. Compounds3, 4, and6 showed moderate acetylcholinesterase inhibitory activity with IC50 values of 7.34, 5.19, and 7.67 μM, respectively. Abstract :